(untitled) (Applied Biological Research, 2016)
Diabetes mellitus is a major disorder of key concern worldwide. So, the plants having anti-diabetic property are of significant interest. Gymnema sylvestre R.Br., a member of family Asclepiadaceae, is a potent anti-diabetic plant. It is a large, woody, much branched, slow growing perennial climber having pubescent young parts. This mesophytic to xerophytic plant is found in tropical to sub